2014
DOI: 10.1007/s00170-014-6258-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental research on electrical discharge machining characteristics of engineering ceramics with different electrical resistivities

Abstract: Electrical discharge machining (EDM) is the extensively used nonconventional material removal process for machining engineering ceramics provided they are electrically conductive. However, the electrical resistivity of the popular engineering ceramics is higher, and there has been no research on the relationship between the EDM parameters and the electrical resistivity of the engineering ceramics that can be machined effectively by EDM. This paper investigates the effects of the electrical resistivity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Lots of researchers have tried to explore the wear law of tool electrode by studying the influences of current, electrical resistivity, pulse duration, hole depth, and tool electrode material on the characteristics of tool electrode wear [10][11][12]. Since the ejectment of debris particles becomes more difficult as the machining depth increases, the tool wear rate increases independent of voltage and workpiece [13].…”
Section: Introductionmentioning
confidence: 98%
“…Lots of researchers have tried to explore the wear law of tool electrode by studying the influences of current, electrical resistivity, pulse duration, hole depth, and tool electrode material on the characteristics of tool electrode wear [10][11][12]. Since the ejectment of debris particles becomes more difficult as the machining depth increases, the tool wear rate increases independent of voltage and workpiece [13].…”
Section: Introductionmentioning
confidence: 98%
“…At present, the special micro-hole machining methods available for engineering ceramics include laser machining, 2,3 ultrasonic machining 4,5 and electrical discharge machining (EDM). 6,7 However, they have several shortcomings such as low machining efficiency and high cost. Laser microfabrication experiments on glass, silicon and ceramics by Rihakova and Chmelickova 2 disclosed that the ultrafast laser can achieve better processing quality.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different abrasive grit sizes (120, 220 and 400) on material removal rate, surface integrity and flexural strength were presented. The effects of EDM parameters (pulse on-time, pulse off-time and peak current) and electrical resistivity on EDM performance of ZnO/ Al 2 O 3 ceramics were studied by Ji et al 6 The results showed that the electrical resistivity of ZnO/Al 2 O 3 ceramics, which could be effectively machined by EDM, increased with the increase in pulse on-time and peak current and with the decrease in pulse off-time.…”
Section: Introductionmentioning
confidence: 99%
“…Micro holes or linear grooves which are straight or inclined on cemented carbide cutting tool rake face or on scrap reeling slot can be obtained conveniently using proper micro tool electrodes and appropriate pulse parameters [22]. Lasting electro-discharge conditions between the micro tool electrode and cemented carbide materials can be improved by high-frequency vibration.…”
Section: Introductionmentioning
confidence: 99%